Deploying a Mental Health Chatbot in Higher Education: The Development and Evaluation of Luna, an AI-Based Mental Health Support System - Phillip Olla; Ashlee Barnes; Lauren Elliott; Mustafa Abumeeiz; Venus Olla; Joseph Tan (Computers, 2025)
Rising mental health challenges among postsecondary students have increased the demand for scalable, ethical solutions. This paper presents the design, development, and safety evaluation of Luna, a GPT-4-based mental health chatbot. Built using a modular PHP architecture, Luna integrates multi-layered prompt engineering, safety guardrails, and referral logic. The Institutional Review Board (IRB) at the University of Detroit Mercy (Protocol #23-24-38) reviewed the proposed study and deferred full human subject approval, requesting technical validation prior to deployment. In response, we conducted a pilot test with a variety of users—including clinicians and students who simulated at-risk student scenarios. Results indicated that 96% of expert interactions were deemed safe, and 90.4% of prompts were considered useful. This paper describes Luna’s architecture, prompt strategy, and expert feedback, concluding with recommendations for future human research trials.